The association between oral health and risk behaviours of university students - Tanzeelah Azam; George Kitsaras; Juliana Gomez; Michaela Goodwin (PLoS ONE, 2025)
Background Young adults are exposed to a variety of risk-related behaviours such as alcohol, smoking, and changes in dietary habits, which may result in unknown outcomes in their oral health. There is limited evidence on whether different risk behaviours are associated with oral health behaviours in the university student population. This study gathers data on the behaviours of students in their first year of university, which will inform the future development of oral health behaviour change interventions for this population. Method This longitudinal quantitative survey involved 205 first-year students aged 18-24 at the University of Manchester. Students completed online questionnaires at baseline and again at a 6-month follow-up interval, providing information regarding self-reported oral health status, hygiene routines, and risk behaviours (e.g., diet, smoking, alcohol). Results The findings showed associations between oral health behaviours with risk behaviours, including links with oral care routines, bleeding gums, brushing frequency, with exercise, vaping, and unhealthy food and drink intake. Significant changes over the two-time points were also observed, including the worsening of the self-reported condition of the teeth (p < 0.001), a reduction in the self-reported condition of the gums (p = 0.004), a decrease in brushing frequency (p = 0.003), fewer regular dental visits (p = 0.013), more students intending to visit their previous dentist rather than finding a new dentist at university (p = 0.026), and greater consumption of unhealthy non-alcoholic drinks (p = 0.003). Positive changes over time included reduced frequency and units of alcohol consumption (p = 0.030 and p = 0.001), fewer instances of binge drinking (p = 0.014), and less frequent consumption of unhealthy foods (p = 0.034). Conclusion The findings highlighted the complex relationship between oral health and risk behaviours in this demographic. Poorer oral health behaviours were linked to engagement in risk behaviours. Thus, oral health behaviours should be targeted alongside other risk behaviours, and tailored interventions should be developed to improve behaviours among university students.